Five new species in the idiocerine genus Busonia Distant (Hemiptera: Cicadellidae: Idiocerinae) from Thailand and Malaysia, with one new record from China - Xue, Qingquan; Zhang, Yalin (Zootaxa, 2015)
Six species in the genus Busonia Distant are described and illustrated, including five new species from Thailand and Malaysia: Busonia curvata, B. fusca, B. lactata, B. micrata, B. serrata, spp. nov., and one newly recorded species from China: Busonia albilateralis Maldonado-Capriles. A redescription of this genus is provided together with a key to species for separation of males.